Cortical hierarchy governs rat claustrocortical circuit organization. Issue 6 (8th February 2016) - White, Michael G.; Cody, Patrick A.; Bubser, Michael; Wang, Hui‐Dong; Deutch, Ariel Y.; Mathur, Brian N.
ABSTRACT: The claustrum is a telencephalic gray matter structure with various proposed functions, including sensory integration and attentional allocation. Underlying these concepts is the reciprocal connectivity of the claustrum with most, if not all, areas of the cortex. What remains to be elucidated to inform functional hypotheses further is whether a pattern exists in the strength of connectivity between a given cortical area and the claustrum. To this end, we performed a series of retrograde neuronal tract tracer injections into rat cortical areas along the cortical processing hierarchy, from primary sensory and motor to frontal cortices. We observed that the number of claustrocortical projections increased as a function of processing hierarchy; claustrum neurons projecting to primary sensory cortices were scant and restricted in distribution across the claustrum, whereas neurons projecting to the cingulate cortex were densely packed and more evenly distributed throughout the claustrum. This connectivity pattern suggests that the claustrum may preferentially subserve executive functions orchestrated by the cingulate cortex. J. Comp. Neurol. 525:1347–1362, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Cortical hierarchy determines the distribution of claustrum projection neurons. Claustral projections to sensory and motor cortices are sparse and exhibit a restricted distribution within the claustrum relative to claustral projections to prelimbic cortex (area 32), whereas claustral projections to cingulate cortex are notably numerous and distributed throughout the claustrum.